2020
DOI: 10.1287/orsc.2019.1300
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Overconfidence and Ambiguity Attitude on Market Entry

Abstract: We study the behavioral drivers of market entry. An experiment allows us to disentangle the impact on entry across different types of markets of two key behavioral mechanisms: overconfidence and attitude toward ambiguity. We theorize and show that the causal effect of overconfidence on entry is limited to skill-based markets and does not appear in those that are chance based. Moreover, we also find that, independent of confidence levels, individuals exhibit ambiguity-seeking behavior when the result of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 87 publications
3
13
0
Order By: Relevance
“…Moreover, the findings are in line with the "Ikea effect," which describes an increased positive valuation of "self"-made products (Hooshangi & Loewenstein 2018). Focusing on the consequences of overconfidence, Gutierrez et al (2020) provided evidence for a causal effect of overconfidence on entering a market, in particular when people believe that the outcome depends on their skills and not on chance.…”
Section: Cognition From a Process Perspectivesupporting
confidence: 65%
“…Moreover, the findings are in line with the "Ikea effect," which describes an increased positive valuation of "self"-made products (Hooshangi & Loewenstein 2018). Focusing on the consequences of overconfidence, Gutierrez et al (2020) provided evidence for a causal effect of overconfidence on entering a market, in particular when people believe that the outcome depends on their skills and not on chance.…”
Section: Cognition From a Process Perspectivesupporting
confidence: 65%
“…The concept of cognitive biases was first introduced by Kahneman and Tversky (1972) as errors in judgment, some of which are related to memory and others to the problem. Heuristic biases relate to mental shortcuts used in decisionmaking (Gutierrez et al, 2020) that often result in systematic errors in judgment (Kahneman and Tversky, 1972). In the stock exchange market, heuristic bias is a common phenomenon that affects investors (Tversky and Kahneman, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…This finding may reflect that those participants may feel more comfortable in dealing with ambiguity resulting in making choices outside best practice recommendations. Previous studies showed that the preference for ambiguity was attributed to overconfidence, which could be a potential explanation for our findings [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 49%